Determination of The Effect of Different Plant Densities and Nitrogen Doses on Agronomical Traits of Sweet Corn (Zea mays saccharata Sturt.) In Conditions of The Northern-East Transitional Region Conditions of Turkey - Senem SABANCI BAL; Mehmet AYÇİÇEK (ISPEC Journal of Agricultural Sciences)
This study was carried out to determine the differences in yield and quality characteristics of different plant density and nitrogen doses in sweet corn (Zea mays L. saccharata Sturt) during 2017 and 2018 years. This research was conducted according to a split-plot design with three replications in the Bingol University Faculty of Agriculture Application and Research Farm. Vega sweet corn hybrid was measured with three intra-row spacing (15, 20, 25 cm) and five pure nitrogen doses (0, 80, 160, 240, 320 N kg ha-1) were grown. In the study, the increasing nitrogen dose showed a significant rise in number of ears per plant , number of kernels per ear, relative chlorophyll content, water-soluble solids content, and fresh ear yield . It was determined that plant density positievly effected fresh ear yield; but the number of kernels per ear, the number of ears per plant, relative chlorophyll content were decreased. The highest fresh ear yield was determined D15 (13106 kg ha-1) in terms of plant density and N3 (15905 kg ha-1)   in terms of nitrogen dose according to the combined experiment years analysis. Considering the average of years, 240 N kg ha-1 (N3) and approximately 100000 plants per hectare (S15) for optimum the fresh ear yield  fertilizer application are recommended.